Motivation of medical staff employed at public polyclinics. The case of Astana. - Makenova, Aigerim; Ybyrayeva, Zumred (Nazarbayev University Graduate School of Public Policy, 2018)
This study reports on the current motivational moods of healthcare workers employed at one of the public polyclinics of Astana. Public healthcare organizations are mostly funded by the state and also have the right to work as an enterprise. Local citizens can get basic primary care within the guaranteed package of services on a free basis. Therefore, the discussions, critique of its limitation, availability, quality of services are usual in Kazakhstan. The current development program “Densaulyk (Health)” contains particular directions for 2016-2019 years. The low motivation of healthcare workers was recognized as one of the problems. The package of benefits and compensation of public healthcare workers is comparatively low in Kazakhstan. The paper describes positive and negative motivation factors of 13 workers employed at one of the public polyclinics of Astana. The main findings identify the factors which motivate health care professionals to work better and keep them at their job places at the polyclinic. Based on a theoretical framework developed by Herzberg (Herzberg, 1959; 1964;1966) we found four main motivational factors, two extrinsic factors including provision of housing and salary and two intrinsic factors including the quality of the management and the status of medical workers relative to the patients.
Keywords: motivational moods of healthcare workers; healthcare workers; public healthcare; public polyclinics